Effect of intake of selected nutrients on skin firmness and elasticity in women - Podgórska, Aleksandra; Kicman, Aleksandra; Naliwajko, Sylwia; Wacewicz-Muczyńska, Marta; Niczyporuk, Marek (Frontiers in Nutrition, 2024)
The proper functioning of the skin is influenced by a proper diet. The purpose of this study was to determine the effect of selected nutrients on selected skin parameters. The study group included 59 women, who were divided into two age groups (under and over 40 years old). A three-day 24-hour dietary interview was conducted among the study women and skin parameters were assessed using the Courage + Khazaka method. The results showed LA, ALA, Dietary fiber, Na, K, Mg, Zn, Cu, Vitamin E, Thiamine, Riboflavin, Folates, Vitamins B6, B12 and C correlated with skin elasticity. On the other hand, skin elasticity is influenced exclusively by vitamin D acted on skin firmness. The results obtained indicate that a diet rich in appropriate nutrients has a positive effect on the proper maintenance of important skin parameters.